METAPHORICAL REPRESENTATIVE OF DISCUSSION TEXT “VIDEO GAMES” - Yenita Uswar (Universitas Potensi Utama, 2021)
This article aims to investigate grammatical metaphor representation in Discussion text. This research was conducted by applying descriptive qualitative research design. The data were taken from a Discussion text from the Internet source with entitled “VIDEO GAMES”. Grammatical metaphor forms when there is a tension or discrepancy between semantics and its coding or realization in grammar or occurs when there is incongruent realization of semantics and lexicogrammar. This text was then analyzed by coding the lexical representation as congruent and incongruent ones. From a Discussion text, the finding is Representation of incongruent coding is only 11% of the text; the rest (89%) is congruent coding. The discussion text addressed the exploration of metaphors in a written text. The grammatical metaphors representation in the text are Verb changes Adjective 28 %, Verb Changes Noun 24 %, Adjective changes Adverb 16 %, Verb to Verb 4 %, Noun to Noun 8 % and adjective to Verb 8 %.